2020
DOI: 10.1111/are.14822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propolis on the immune enhancement of the formalin‐inactivated Aeromonas salmonicida vaccine

Abstract: Furunculosis caused by Aeromonas salmonicida is a major threat to salmonids throughout all their life stages. Vaccination against A. salmonicida has been shown to provide effective protection in aquaculture. The success of many vaccines relies on their association with the appropriate adjuvant to increase their immunogenicity and ensure long-term protection. In this study, the effects of vaccines using propolis as adjuvants against furunculosis in rainbow trout (Oncorhynchus mykiss) were evaluated. The paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Romstad et al (2012) indicated that Atlantic salmon immunized with A-layer positive vaccines demonstrated an increased mean antibody response with rising antigen dose [ 77 ]. According to Liu et al (2020), all the immunized groups had noticeably higher antibody levels post vaccination in comparison to the control group [ 78 ]. Rising the antibody was consistent with what we observed in this study after boosting ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Romstad et al (2012) indicated that Atlantic salmon immunized with A-layer positive vaccines demonstrated an increased mean antibody response with rising antigen dose [ 77 ]. According to Liu et al (2020), all the immunized groups had noticeably higher antibody levels post vaccination in comparison to the control group [ 78 ]. Rising the antibody was consistent with what we observed in this study after boosting ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR was performed on an ABI 7500 Real-Time PCR System using the kit (TOYOBO, Osaka, Japan). The RT-qPCR reactions were carried out following the procedures described by Liu et al [29]. The relative gene expression level was analyzed using the 2 −∆∆CT method [30].…”
Section: Gene Expression Analysismentioning
confidence: 99%